Indirect Method for Determination Desferal in Pure and Pharma-ceutical Formulations Using Cerium (IV) As a Chelating Element - Ashraf Saad Rasheed (Journal of Global Pharma Technology, 2016)
Objective: The present study includes indirect analytical method for the determination of the drug desferal (DSFM) in some pharmaceutical dosages using molecular absorption. DSFM was usually used for treating such diseases like Thalasemia and Alzheimer. Methods: The proposed method is built on reaction between DSFM and cerium (IV) ion to forms an orange chelate complex (λ max = 443 nm) at pH 6. Results: The optimal experimental condition for the chelate formation: pH=6; concentration of Ce(IV) (30 mg L-1); maximum reaction time (10 min.); lmax=443 nm; metal -to- ligand (1:1) ratio.  Analytical figures of merits: linear dynamic range (1-110) mg L-1; r = 0.9996, S = 0.9996 mg.cm-2), D.L (0.167) mg L-1; Erel. % 1.26; recovery% 100.2; RSD% 1.460.Conclusion: The developed method was successfully applied to the estimate of DSFM in pharmaceutical samples.Keywords: Desferal, Spectrophotometric, Cerium sulfate tetrahydrate, Pharmaceutical dosages.